Behavioral and electrophysiological evidence of opposing lateral visuospatial asymmetries in the upper and lower visual fields. (February 2015) - Loughnane, Gerard M.; Shanley, John P.; Lalor, Edmund C.; O'Connell, Redmond G.
Abstract: Neurologically healthy individuals typically exhibit a subtle bias towards the left visual field during spatial judgments, known as "pseudoneglect". However, it has yet to be reliably established if the direction and magnitude of this lateral bias varies along the vertical plane. Here, participants were required to distribute their attention equally across a checkerboard array spanning the entire visual field in order to detect transient targets that appeared at unpredictable locations. Reaction times (RTs) were faster to left hemifield targets in the lower visual field but the opposite trend was observed for targets in the upper field. Electroencephalogram (EEG) analyses focused on the interval prior to target onset in order to identify endogenous neural correlates of these behavioral asymmetries. The relative hemispheric distribution of pre-target oscillatory alpha power was predictive of RT bias to targets in the lower visual field but not the upper field, indicating separate attentional mechanisms for the upper and lower visual fields. Analysis of multifocal visual-evoked potentials (MVEP) in the pre-target interval also indicated that the opposing upper and lower field asymmetries may impact on the magnitude of primary visual cortical responses. These results provide new evidence of a functional segregation of upper and lower field visuospatial processing.